Kinetics of transesterification of palm oil under conventional heating and microwave irradiation, using CaO as heterogeneous catalyst. (15th September 2016) - Ye, Wei; Gao, Yujie; Ding, Hui; Liu, Mingchao; Liu, Shejiang; Han, Xu; Qi, Jinlong
Highlights: A transesterification kinetics model was established under two heating methods. The total reaction order under conventional heating method was 1. The total reaction order under microwave irradiation was 3. Microwave significantly accelerated the transesterification reaction rate. CaO was used as heterogeneous catalyst. Abstract: In the present study, the kinetics of transesterification of palm oil was explored under conventional heating and microwave irradiation, using CaO as heterogeneous catalyst. The optimal experimental conditions were, microwave power of 150 W, alcohol to oil molar ratio of 9:1, catalyst of 5%, stirring speed of 450 r/min and reaction time of 60 min. By establishing kinetic models, the total reaction orders of transesterification under the two heating methods were figured out. The total reaction order under conventional heating was 1, while 3 under microwave irradiation, which indicated that microwave irradiation could increase the overall reaction order and accelerate the conversion rate for biomass to biodiesel.